A Correlational Study on Mindset, Grit, and Adversity Quotient of Pre-Service Teachers: Evidence in Philippines and Hongkong - Alberto D. Yazon; Karen Ang-Manaig; Ting Wai Ching Adrian (Research Synergy Foundation, 2021)
Understanding pre-service teachers' mindset, grit, and adversity quotient boosts their morale, confidence, and self-esteem as future educators. This descriptive-correlational research determined the relationship between the aforementioned constructs of pre-service teachers in the Philippines and Hong Kong. The respondents of the study were 155 pre-service teachers from two Asian countries. The data were gathered through answering an online questionnaire generated through Google forms and disseminated through e-Mail and messenger on social networking sites. The responses from the respondents were automatically stored at the Google drive application. The standardized questionnaires were used in the study. The respondent's mindset was assessed using Dweck's Mindset Instrument (DMI). In terms of grit, it was measured using Duckworth's Grit-Short Scale, and the respondent's adversity quotient was examined using The Adversity Quotient Profile® 9.1 by Dr. Paul G. Stoltz. The majority of the pre-service teachers in the two Asian countries are dominated by female students with an ideal age bracket suited as university students possessing a growth mindset. Students with a growth mindset have displayed a higher level of grit and adversity quotients than those students with a fixed mindset. This study concluded that mindset and adversity quotient is significantly associated. Hence, stakeholders involved in the development of 21st-century learners should promote the mindset, but they may also develop other essential parallel variables, such as the adversity quotient, to encourage them to be desirable attribution necessary for being global and competitive citizens of the society.